2017
DOI: 10.1111/1471-0528.15027
|View full text |Cite
|
Sign up to set email alerts
|

Drug interactions between rifamycin antibiotics and hormonal contraception: a systematic review

Abstract: Rifampin and rifabutin reduce systemic exposure of oral contraceptives, but no studies have evaluated pregnancy risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 27 publications
0
25
1
Order By: Relevance
“…intrauterine devices or condoms) which are not adversely affected by rifamycins, as hormonal contraception cannot be relied upon during tuberculosis treatment. 85 Pregnancy testing should be performed prior to provision of therapy so that pregnant adolescents can be appropriately referred for prenatal care. Testing for other sexually-transmitted infections should be offered at the time adolescents are tested for HIV infection, as incidence rates are usually highest in this age group.…”
Section: Specific Considerations For Adolescents During Tuberculosis mentioning
confidence: 99%
“…intrauterine devices or condoms) which are not adversely affected by rifamycins, as hormonal contraception cannot be relied upon during tuberculosis treatment. 85 Pregnancy testing should be performed prior to provision of therapy so that pregnant adolescents can be appropriately referred for prenatal care. Testing for other sexually-transmitted infections should be offered at the time adolescents are tested for HIV infection, as incidence rates are usually highest in this age group.…”
Section: Specific Considerations For Adolescents During Tuberculosis mentioning
confidence: 99%
“…The study population comprised 364 women with a median age of 23 [interquartile range (IQR) [19][20][21][22][23][24][25][26][27][28][29]. Of these, 40…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been suggested that use of antibiotics in general might influence the use of oral contraceptives [20,21]. With the exception of rifampicin, which has been shown to confer a risk of oral contraceptive failure [22], this alleged risk has largely been 'debunked' [23]. Importantly, the putative mechanism for such interactions is that of altered enterohepatic recirculation of hormones [24] and not of induction of CYP enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…5,12 Strikingly, in 73% of the cases included in the systematic review by Sobhy et al, the pregnancy occurred after TB was diagnosed, rather than TB being diagnosed in the course of the pregnancy. 5 Rifamycins adversely affect the metabolism of contraceptive hormones, 27 and women being treated for TB should be provided information about and access to effective contraception (such as injectable depot medroxyprogesterone acetate, which does not appear to be affected by rifampicin, either copper or intrauterine devices, or barrier methods 28 ). There is limited evidence on the impact of rifampicin on the effectiveness of progesterone-only contraception compared to combined oral contraceptive pill.…”
Section: Consequences Of Tb In Pregnancymentioning
confidence: 99%